The future in the litter bin – bioconversion of food waste as driver of a circular bioeconomy - Razouk, Afraa; Tiganescu, Eduard; von Glahn, Anthea Julia; Abdin, Ahmad Yaman; Nasim, Muhammad Jawad; Jacob, Claus (Frontiers in Nutrition, 2024)
Bioconversion of organic waste requires the development and application of rather simple, yet robust technologies capable of transferring biomass into energy and sustainable materials for the future. Food waste plays a significant role in this process as its valorisation reduces waste and at the same time avoids additional exploitation of primary resources. Nonetheless, to literally become “litterate”, extensive research into such robust large-scale methods is required. Here, we highlight some promising avenues and materials which fulfil these “waste to value” requirements, from various types of food waste as sustainable sources for biogas, bioethanol and biodiesel to fertilizers and antioxidants from grape pomace, from old-fashioned fermentation to the magic of anaerobic digestion.